ELECTROMYOGRAM OF THE ALIMENTARY TRACT BY CHRONICALLY IMPLANTED BIPOLAR ELECTRODES - KUWASHIMA, Teruo; HUKUDA, Tetsuo; KURAMOTO, Morio; KONEGAWA, Ryuji; Komi, Nobuhiko; TAKITA, Shuhei (Japanese Journal of Smooth Muscle Research, 1975)
For the long term observation of the electrical activity of the canine alimentary tract, a bipolar silver electrode was devised in our laboratory. The electrode has been demonstrated to be satisfactory in sensing the electrical activity of the alimenatry tract. The electromygoram of the esophagus was consisted of very fast spike burst lasting for about 3 to 5 seconds in swallowing actions. The stomach showed a cyclically recurring basic electrical rhythm (BER), which was propagated caudally, and spike burst which was related to the contractile activity of the gastric smooth muscle. The duodenum and small bawel also showed both BER and spike burst in their electrical activity. Thus the electromyograms obtained by our electrode have shown their similarity to those by monopolar electrodes. Furthermore, our electrode has proved its durability, functioning for more than 5 months. Details of the construction of our electrode were described.